Construindo o turismo de base comunitária na Ilha das Couves em Ubatuba, SP (Brasil) - Rosa, Thais Felipe (2023)
This research investigated the socioeconomic practice of tourism associated with the conservation of cultural and natural heritage on Ilha das Couves, located in Ubatuba, on the northern coast of São Paulo, Brazil. The focus was on Community- Based Tourism, which emphasizes the active participation of traditional communities in planning more sustainable tourism activities. The study prioritized listening to the Caiçara community of Vila de Picinguaba, a pioneer in the construction and organization of this tourism model on Ilha das Couves, as well as other stakeholders involved. The island has faced problems arising from mass tourism since 2016, which resulted in the degradation of its natural and cultural heritage. These challenges began to be resolved in 2019, with the adoption of normative ordinances prepared by institutions such as the Forestry Foundation, the APA Marinha, the Federal Public Prosecutor's Office of Caraguatatuba, the Traditional Communities Forum, and the local community involved in tourism itself. The ordinances (315/2019, 323/2020, 328/2021, 350/2022, 387/2023) established guidelines for controlling and organizing the flow of tourists, as well as for the sustainable use of space. Based on these measures, the Caiçara community of Vila de Picinguaba, together with the Traditional Communities Forum, structured proposals for Community- Based Tourism for the Island. At the time this research was carried out, the organization had 52 members, 38 of whom were boatmen and 14 professionals that were majority women who worked in tourist reception. The research used qualitative methods, including 66 semi-structured interviews — 21 conducted online and 45 in person — with community leaders, members of local communities, representatives of public and private institutions, tourists and others involved in Community-Based Tourism. In addition, four technical visits were made to the region to collect data on site, following the guidelines of the World Health Organization and respecting the interests of local communities. Through a literature review and interviews with the various stakeholders in the network, it was found that Community-Based Tourism, combined with monitoring the island's support capacity, was essential to promoting sustainable tourism development. This model generated cooperation and motivation around common goals. It is important to note that each community has unique characteristics and must independently define the best way to implement its Community-Based Tourism itinerary, considering that this process is gradual and requires support from municipal, state and federal government spheres.